2021
DOI: 10.29309/tpmj/2021.28.04.6052
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of the patients admitted in PICU in tertiary hospital.

Abstract: Objectives: To analyze the clinical profile, etiologies and outcome of seriously ill patients admitted in Pediatric Intensive Care Unit (PICU). Study Design: Cross Sectional study. Setting: PICU of Nishtar Medical Hospital, Multan, Pakistan. Period: January 2018 to December 2018. Material & Methods: During the study period, a total of 150 children, aged 1 to 12 years, with better prognosis and post-surgical cases requiring intensive care were registered. Age, gender, cause for hospitalization (clinical, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This study showed that, the overall mortality rate for children was 37.7%. Regarding study by Saleem et al (10) who enrolled 150 children admitted in PICU at Pakistan, they recorded 18% as a mortality rate. Alsuheel et al (11) also conducted a study in Saudi Arabia with mortaliy rate was(37.4%) .…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that, the overall mortality rate for children was 37.7%. Regarding study by Saleem et al (10) who enrolled 150 children admitted in PICU at Pakistan, they recorded 18% as a mortality rate. Alsuheel et al (11) also conducted a study in Saudi Arabia with mortaliy rate was(37.4%) .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, HMD was the most communal ventilation indication. In the studies of Riyas et al, Singh et [16][17] . Preterm infant apnoea is the next most important indication for ventilation with a 61.5% survival rate in our study.…”
Section: Discussionmentioning
confidence: 99%